Te-doped double perovskite Cs2Zr1-xSnxCl6 solid solution material as well as preparation method and application thereof

Through the development of Te-doped double perovskite Cs2Zr1-xSnxCl6 solid solution material, the problem of poor performance of existing optical storage materials in low temperature environments is solved, and efficient X-ray optical storage is achieved, suitable for applications within the ultra-wide temperature range, and production costs are reduced.

CN119505901AActive Publication Date: 2025-02-25HUAQIAO UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411669697.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

Existing optical storage materials have poor performance, are prone to moisture absorption and slow response speed in low temperature environments, which limits their application range and are not suitable for extreme environments such as aerospace equipment or polar detectors.

Method used

A Te-doped double perovskite Cs2Zr1-xSnxCl6 solid solution material was developed to improve the material's hygroscopic resistance, chemical stability and X-ray-induced carrier storage volume by doping Te4+ ions and adjusting Sn content, thereby achieving high-efficiency optical storage in an ultra-wide temperature range.

Benefits of technology

The material has high moisture resistance and chemical stability, and can effectively store carriers in a wide temperature range of 100K to 400K. It is suitable for X-ray imaging and structural detection at ultra-wide temperatures, and has a low production cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505901A_ABST
    Figure CN119505901A_ABST
Patent Text Reader

Abstract

The invention discloses a Te-doped double perovskite Cs2Zr1-xSnxCl6 solid solution material as well as a preparation method and application thereof, the Te-doped double perovskite Cs2Zr1-xSnxCl6 solid solution material has a chemical general formula of Cs2Zr1-xSnxCl6: yTe < 4 + >, x is greater than 0 and less than 1, y is greater than 0 and less than 0.2, the Te-doped double perovskite Cs2Zr1-xSnxCl6 solid solution material can be prepared through a solvothermal method reaction under a relatively low reaction condition, and the Te-doped double perovskite Cs2Zr1-xSnxCl6 solid solution material can be used for preparing the Te-doped double perovskite solid solution material. The material has relatively high moisture absorption resistance, chemical stability and X-ray induced carrier storage capacity, and the carrier storage temperature covers an ultra-wide temperature range from 100K to 400K.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of optical storage materials, and specifically relates to a Te-doped double perovskite Cs2Zr 1-x Sn x Cl6 solid solution material, preparation method and application thereof. Background Art

[0002] With the rapid development of society and technology, the amount of data generated continues to rise, and how to efficiently store and access this data has become a matter of great concern. The research and development of new optical storage materials is a key approach to addressing this challenge. These materials are usually composed of inorganic compounds, mainly including a crystal matrix, an electron capture region, and a hole capture region. When irradiated with high-energy radiation (such as X-rays), optical storage materials can generate free carriers (electrons and holes). Some of these free carriers will be captured in the capture centers of electrons and holes. Through external physical stimulation, such as mechanical force or heat, the electrons or holes stored in the capture center can be released. When electrons combine with holes, the released energy causes the recombination center to transition from the ground state to the excited state, and then the recombination center emits a photon when it returns from the excited state to the ground state. It is precisely because of this unique luminescence property that optical storage materials have been widely used in fields such as X-ray imaging and information storage. Therefore, continuing to develop new optical storage materials has significant scientific research value and practical application potential for improving data storage.

[0003] BaFBr(I):Eu 2+ It is a common alkaline earth halide optical storage material, mainly used in X-ray detectors, imaging systems (such as computed tomography CT) and fluorescence analysis. However, in low-temperature environments, its excited state Eu2+ is difficult to effectively radiate and recombine, resulting in a decrease in luminescence brightness, which makes it unsuitable for applications in extremely low-temperature environments (such as aerospace equipment or polar detectors). BaFBr(I) is a hygroscopic material that is easily hydrolyzed or degraded in a humid environment, resulting in a decrease in optical properties or material failure. This requires it to be sealed or operated in a dry environment during use, which increases the difficulty of application. In addition, long-term use or exposure to strong light will cause BaFBr(I):Eu 2+ The efficiency may be reduced, which is related to the migration or energy level change of Eu2+ ions in the crystal. 2+The process conditions are harsh, requiring ultra-high temperature (>1000℃) and reducing atmosphere (H2) and strict control of the purity of the raw materials. In particular, the material needs to be prevented from being oxidized during the process of adding iodine (I-) and optimizing the Eu2+ doping concentration, which leads to a high production cost of BaFBr(I)2+. In summary, although BaFBr(I)2+ has advantages in certain imaging and detection fields, its poor performance in low temperature environments, easy moisture absorption, and slow response speed limit its application. If it needs to be used under low temperature or humid conditions, new alternative materials need to be developed urgently. Summary of the invention

[0004] The purpose of the present invention is to provide a Te-doped double perovskite Cs2Zr 1-x Sn x Cl6 solid solution material and preparation method and application thereof, the Te-doped double perovskite Cs2Zr 1-x Sn x The Cl6 solid solution material has high anti-hygroscopicity, chemical stability and X-ray-induced carrier storage capacity, and the carrier storage temperature covers an ultra-wide temperature range from 100K to 400K.

[0005] The technical solution of the present invention is as follows:

[0006] A Te-doped double perovskite Cs2Zr 1-x Sn x Cl6 solid solution material, its chemical formula is Cs2Zr 1-x Sn x Cl6:yTe 4+ , where 0<x<1, 0<y<0.2.

[0007] In some possible implementations, the crystal structure is cubic and the space group is

[0008] In some possible implementations, it is obtained by heat treating a cesium-containing compound, a zirconium-containing compound, a tin-containing compound, a chlorine-containing compound and a tellurium-containing compound, wherein the heat treatment temperature is 170 to 200° C. and the heat treatment time is 0.5 to 24 hours.

[0009] In some possible implementations, the cesium-containing compound is cesium chloride and / or cesium carbonate, the zirconium-containing compound is zirconium chloride, the tin-containing compound is at least one of tin tetrachloride, tin dioxide and stannous oxide, the chlorine-containing compound is hydrochloric acid, and the tellurium-containing compound is tellurium dioxide and / or tellurium tetrachloride.

[0010] A Te-doped double perovskite Cs2Zr 1-x Sn xThe preparation method of Cl6 solid solution material, the chemical formula of the Te doped double perovskite solid solution material is Cs2Zr 1-x Sn x Cl6:yTe 4+ , wherein 0<x<1, 0<y<0.2, and the preparation method comprises the following steps:

[0011] (1) Weighing a cesium-containing compound, a zirconium-containing compound, a tin-containing compound, a chlorine-containing compound and a tellurium-containing compound in a molar ratio of 2:1-x:x:6:y;

[0012] (2) The cesium-containing compound, the zirconium-containing compound, the tin-containing compound, the chlorine-containing compound and the tellurium-containing compound are mixed and placed in a sealed reaction vessel, and heat-treated at 170 to 200° C. for 0.5 to 24 hours, and then cooled to obtain the product.

[0013] In some possible implementations, the specific operation of the heat treatment is as follows: increase the temperature from room temperature to 170-200°C at a heating rate of 1-3°C / min, keep warm for 0.5-24 hours, then cool to room temperature at a cooling rate of 2-20°C / hour, separate and retain the solids after cooling, and the product is ready.

[0014] In some possible implementations, the cesium-containing compound is cesium chloride and / or cesium carbonate, the zirconium-containing compound is zirconium chloride, the tin-containing compound is at least one of tin tetrachloride, tin dioxide and stannous oxide, the chlorine-containing compound is hydrochloric acid, and the tellurium-containing compound is tellurium dioxide and / or tellurium tetrachloride.

[0015] In some possible implementations, after the solid matter is separated and retained, the following operations are further included: washing and drying the solid matter. For example, in the example, the washing agent is ethanol.

[0016] In some possible implementations, the cesium-containing compound, the zirconium-containing compound and the tin-containing compound in step (1) are weighed in a protective atmosphere. The tellurium-containing compound and the chlorine-containing compound can be weighed together in a protective atmosphere or directly in air. As in the example, the protective atmosphere can be a nitrogen atmosphere or a rare gas atmosphere.

[0017] In some possible implementations, step (2) is performed in a closed air atmosphere.

[0018] The above Te-doped double perovskite Cs2Zr 1-x Sn x Application of Cl6 solid solution materials in the preparation of optical storage materials.

[0019] A light storage material, the raw material of which includes the above-mentioned Te-doped double perovskite Cs2Zr 1-x Sn x Cl6 solid solution material.

[0020] The present invention has at least the following beneficial effects:

[0021] (1) Te-doped double perovskite Cs2Zr of the present invention 1-x Sn x Cl6 solid solution material has high moisture resistance and chemical stability, and can be effectively excited by X-ray high-energy photons to generate high carrier storage. 4+ Not only does it serve as an efficient hole capture and luminescence recombination center, but also Te 4+ In Cs2Zr 1-x Sn x Doping in Cl6 can induce a large number of electron trap centers with electron capture characteristics. Furthermore, by adjusting the Sn content, the thermoluminescence peak position can be adjusted in a wide temperature range of 100K to 400K. The material can be used in fields such as X-ray imaging and structural detection that can work in ultra-wide temperatures.

[0022] (2) Te-doped double perovskite Cs2Zr 1-x Sn x Only Te is used in Cl6 solid solution materials 4+ The single doping of ions can produce efficient X-ray optical storage materials. Compared with the traditional optical storage materials co-doped with multiple rare earth luminescent ions, Cs2Zr 1-x Sn x Cl6:Te 4+ Solid solution optical storage materials have highly reproducible luminescence properties and low production costs.

[0023] (3) The present invention adopts a solvent thermal reaction method to generate Te-doped double perovskite Cs2Zr with high crystallinity and carrier storage at 170-200°C. 1-x Sn x Compared with the harsh conditions of ultra-high temperature (>1000 degrees Celsius) and reducing atmosphere (H2) of traditional optical storage materials, the Cl6 solid solution material has simple reaction conditions and operations and low production costs. In addition, the equipment required for this method is mature and simple in structure, which is convenient for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The Te-doped double perovskite Cs2Zr prepared in Examples 1 to 3 1-x Sn x X-ray diffraction pattern of Cl6 solid solution material;

[0025] Figure 2 The Te-doped double perovskite solid solution Cs2Zr prepared in Examples 1 to 3 1-x Sn xThermoluminescence spectrum curve of Cl6 material after being excited by X-rays, and the Te-doped double perovskite Cs2Zr prepared in Example 1 1-x Sn x Comparison of the Cl6 solid solution material under sunlight and after being excited by X-ray light;

[0026] Figure 3 The Te-doped double perovskite Cs2Zr prepared in Example 1 1-x Sn x Thermoluminescence emission spectrum of Cl6 solid solution material after being excited by X-rays;

[0027] Figure 4 The Te-doped double perovskite Cs2Zr prepared in Example 1 1-x Sn x The relationship between the absolute afterglow intensity of Cl6 solid solution material at room temperature and time after being excited by X-rays;

[0028] Figure 5 The Te-doped double perovskite Cs2Zr prepared in Example 2 1-x Sn x Thermoluminescence emission spectrum of Cl6 solid solution material after X-ray excitation;

[0029] Figure 6 The Te-doped double perovskite Cs2Zr prepared in Example 2 1-x Sn x Comparison of afterglow emission spectra of Cl6 solid solution material at 140K (Kelvin) after being excited by X-ray;

[0030] Figure 7 The Te-doped double perovskite Cs2Zr prepared in Example 3 1-x Sn x Thermoluminescence emission spectrum of Cl6 solid solution material after X-ray excitation;

[0031] Figure 8 The Te-doped double perovskite Cs2Zr prepared in Example 4 1-x Sn x Thermoluminescence emission spectrum of Cl6 solid solution material after X-ray excitation. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further illustrated and described below through specific implementation methods.

[0033] In the following examples, the water used can be one or more of distilled water, purified water, and drinking water; unless otherwise specified, the detection methods in the following examples are conventional detection methods; the reagents in the following examples are purchased from commercial channels unless otherwise specified.

[0034] Example 1

[0035] Te-doped double perovskite Cs2Zr of Example 1 1-x Sn x Cl6 solid solution material is Cs2Zr 0.75 Sn 0.25 Cl6:0.01Te 4 + Solid solution material, based on this chemical formula, calculate the preparation of Cs2Zr 0.75 Sn 0.25 Cl6:0.01Te 4+ The chemical raw materials required for the solid solution material are: 0.3367 grams of cesium chloride (CsCl), 0.1748 grams of zirconium chloride (ZrCl4), 0.0651 grams of tin chloride (SnCl4), 0.00159 grams of tellurium dioxide (TeO2) and 8 mL of 12 mol / L hydrochloric acid (HCl) solution.

[0036] The preparation method thereof comprises the following steps:

[0037] (1) In a glove box filled with nitrogen, 0.3367 g of cesium chloride, 0.1748 g of zirconium chloride and 0.0651 g of tin chloride were accurately weighed, and 0.00159 g of tellurium dioxide was accurately weighed in an air atmosphere. These four raw materials were placed in a small glass bottle, and then 8 mL of a 12 mol / L hydrochloric acid solution was added.

[0038] (2) After the raw materials in the small glass are mixed evenly, they are transferred to the lining of the hydrothermal reactor. The hydrothermal reactor is placed in a high-temperature furnace for heat treatment. The sample is heated from room temperature to 180°C in 1 hour, kept at 180°C for 12 hours, and then cooled to room temperature at a cooling rate of 2.5°C / hour. After the sample is cooled to room temperature, the solution in the lining of the reactor is poured out, the crystals in the lining are cleaned with ethanol, and dried at 60°C for 0.5 hours to obtain Cs2Zr 0.75 Sn 0.25 Cl6:0.01Te 4+ Solid solution materials.

[0039] In order to verify the crystal structure of the synthesized samples, Figure 1 The Cs2Zr prepared in Example 1 is given 0.75 Sn 0.25 Cl6:0.01Te 4+ X-ray diffraction spectrum of solid solution material. The spectrum was measured using a Bruker D8Advance device, with the X-ray tube voltage set to 40kV and the current set to 30mA. Figure 1 It can be seen from the X-ray spectrum that the Cs2Zr0.75 Sn 0.25 Cl6:0.01Te 4+ The solid solution material has the same crystal structure as Cs2ZrCl6 (PDF#74-0505). 4 + The doping did not lead to the generation of new impurities.

[0040] Figure 2 The Cs2Zr of Example 1 is given 0.75 Sn 0.25 Cl6:0.01Te 4+ Thermoluminescence curve of solid solution material. Thermoluminescence curve test process is: the sample is cooled to 100K, excited with X-ray for 70 seconds, and then the sample is heated at a heating rate of 1K / s, while monitoring the change of sample luminescence intensity with temperature. The X-ray dose is about 6.94mGy. In order to make the luminescence intensity comparable, Figure 2 The sample mass and the X-ray excitation time were calibrated. Figure 2 It can be seen that Cs2Zr 0.75 Sn 0.25 Cl6:0.01Te 4+ The thermoluminescence curve of Cs2Zr is mainly composed of two thermoluminescence bands with peaks at 158K and 228K. The thermoluminescence curve covers the temperature range from 100K to 400K. 0.75 Sn 0.25 Cl6:0.01Te 4+ The integrated thermoluminescence intensity is the commercial long afterglow material Y2O2S:Eu 3+ In addition, Figure 2 The Cs2Zr of Example 1 is also given. 0.75 Sn 0.25 Cl6:0.01Te 4+ Room temperature photo of solid solution material and room temperature afterglow photo after X-ray excitation. After X-ray excitation stops, Cs2Zr 0.75 Sn 0.25 Cl6:0.01Te 4+ The room temperature afterglow intensity can reach 220mcd / m 2 .

[0041] Figure 3 Cs2Zr of Example 1 0.75 Sn 0.25 Cl6:0.01Te 4+Thermoluminescence emission spectrum of solid solution material. The sample was first cooled to 100K, then excited with X-ray for 500 seconds, and the relationship between its luminescence spectrum and temperature was measured. The setting conditions of the X-ray tube were 45kV, 70μA, 3.15W. The heating rate of the thermoluminescence emission spectrum was 1K / s. Figure 3 It can be seen that at low temperature of 169K, its thermoluminescence emission spectrum consists of a broad emission band with a peak at ~582nm (nanometers) and a shoulder-shaped peak at ~750nm. The entire emission spectrum covers a wavelength range from 450 to 1000nm. At a relatively high temperature of 239K, the thermoluminescence emission spectrum consists of a peak at ~582nm Te 4+ Emission belt composition.

[0042] Figure 4 Cs2Zr of Example 1 0.75 Sn 0.25 Cl6:0.01Te 4+ The absolute decay curve of the room temperature afterglow of the solid solution material. Before testing the absolute afterglow, the sample was excited by X-rays at room temperature (295K) for 500 seconds. The setting conditions of the X-ray tube were 58kV, 190μA, 11W. Figure 4 It can be seen that the Cs2Zr of Example 1 0.75 Sn 0.25 Cl6:0.01Te 4+ The room temperature afterglow of the solid solution material exceeds 1.1 hours. After 1.1 hours of decay, Cs2Zr 0.75 Sn 0.25 Cl6:0.01Te 4+ The afterglow intensity is 4687 times that of the background signal. This shows that the Cs2Zr 0.75 Sn 0.25 Cl6:0.01Te 4+ Solid solution materials have high X-ray-induced carrier storage properties.

[0043] Example 2

[0044] Te-doped double perovskite Cs2Zr of Example 2 1-x Sn x Cl6 solid solution material is Cs2Zr 0.5 Sn 0.5 Cl6:0.01Te 4+ Based on this chemical formula, the preparation of Cs2Zr 0.5 Sn 0.5 Cl6:0.01Te 4+The chemical raw materials required for the solid solution material are: 0.3367 grams of cesium chloride (CsCl), 0.1165 grams of zirconium chloride (ZrCl4), 0.1303 grams of tin chloride (SnCl4), 0.00159 grams of tellurium dioxide (TeO2) and 10 mL of 12 mol / L hydrochloric acid (HCl) solution.

[0045] The preparation method thereof comprises the following steps:

[0046] (1) In a nitrogen-protected glove box, accurately weigh 0.3367 g of cesium chloride, 0.1165 g of zirconium chloride, and 0.1303 g of tin chloride, and accurately weigh 0.00159 g of tellurium dioxide in air. Place these four raw materials in a small glass bottle, and then add 10 mL of 12 mol / L hydrochloric acid solution.

[0047] (2) Stir the chemical raw materials in the small glass bottle with a glass rod to mix them evenly, and then transfer them to the lining of the reactor for heat treatment. The sample is heated from room temperature to 185°C over 2 hours, kept at 185°C for 10 hours, and then cooled to room temperature at a cooling rate of 2.5°C / hour. Open the reactor, take out the lining, pour out the excess solution in the lining, and you can get Cs2Zr in Example 2. 0.5 Sn 0.5 Cl6:0.01Te 4+ of solid solution materials.

[0048] Figure 1 The Cs2Zr of Example 2 is given 0.5 Sn 0.5 Cl6:0.01Te 4+ X-ray diffraction spectrum of solid solution material. Its diffraction peaks are similar to those of standard substances Cs2SnCl6 (PDF#70-2413) and Cs2ZrCl6 (PDF#74-0505). This shows that Cs2Zr 0.5 Sn 0.5 Cl6:0.01Te 4+ The solid solution material has a similar crystal structure to the reference materials Cs2SnCl6 (PDF#70-2413) and Cs2ZrCl6 (PDF#74-0505). 4+ The doping did not induce any obvious impurity phase.

[0049] Figure 2 The Cs2Zr of Example 2 is given 0.5 Sn 0.5 Cl6:0.01Te 4+Thermoluminescence curve of solid solution material after being excited by X-rays. Its thermoluminescence curve mainly consists of two thermoluminescence bands with peaks at ~150K and ~210K. The thermoluminescence curve covers the temperature range of 100K to 350K. 0.5 Sn 0.5 Cl6:0.01Te 4+ The integrated thermoluminescence intensity of the solid solution material is the commercial long afterglow material Y2O2S:Eu 3+ This indicates that Cs2Zr 0.5 Sn 0.5 Cl6:0.01Te 4+ Has high carrier storage.

[0050] Figure 5 The Cs2Zr of Example 2 is given 0.5 Sn 0.5 Cl6:0.01Te 4+ Thermoluminescence emission spectrum of solid solution material after being excited by X-rays. Cs2Zr 0.5 Sn 0.5 Cl6:0.01Te 4+ The emission spectrum of solid solution materials is temperature dependent. At low temperatures, such as 150K, in addition to the Te 4+ The characteristic luminescence band of the thermoluminescent material is not only the peak of the Te emission band, but also the shoulder emission band with a peak at about 750nm. As the temperature increases, for example at 209K and 295K, the thermoluminescence emission spectrum is mainly composed of the peak of Te at ~582nm. 4+ It is composed of characteristic luminous bands.

[0051] Figure 6 The Cs2Zr of Example 2 is given 0.5 Sn 0.5 Cl6:0.01Te 4+ Afterglow emission spectrum of solid solution material at 140K after 300 seconds of X-ray excitation. The setting conditions of the X-ray tube are 45kV, 70μA, 3.15W. Figure 6 It can be seen that the Cs2Zr of Example 2 0.5 Sn 0.5 Cl6:0.01Te 4+ The solid solution material can emit an ultra-broadband afterglow luminescence from 500nm to 1000nm for more than 60 seconds, which indicates that it has a high current storage capacity.

[0052] Example 3

[0053] Te-doped double perovskite Cs2Zr of Example 3 1-x Sn x Cl6 solid solution material is Cs2Zr0.25 Sn 0.75 Cl6:0.01Te 4 + Solid solution material, based on this chemical formula, calculate the preparation of Cs2Zr 0.25 Sn 0.75 Cl6:0.01Te 4+ The chemical raw materials required are: 0.3367 grams of cesium chloride (CsCl), 0.0583 grams of zirconium chloride (ZrCl4), 0.1954 grams of tin chloride (SnCl4), 0.00159 grams of tellurium dioxide (TeO2) and 12mL of 12mol / L hydrochloric acid (HCl) solution.

[0054] The preparation method thereof comprises the following steps:

[0055] (1) In a nitrogen-protected glove box, accurately weigh the required 0.3367 g of cesium chloride, 0.0583 g of zirconium chloride, 0.1954 g of tin chloride (SnCl4), and 0.00159 g of tellurium dioxide (TeO2), and transfer the raw materials into a small glass bottle. Place the small glass bottle in an air atmosphere and quickly add 12 mL of 12 mol / L hydrochloric acid solution.

[0056] (2) The raw materials in the small glass are mixed evenly and then transferred to the inner lining of the high-temperature reactor. A polytetrafluoroethylene inner cover is added to the inner lining to keep the reactants and raw materials in a closed environment. The reactor is heated evenly from room temperature to 200°C over 2 hours, and kept at 200°C for 24 hours, and finally cooled to room temperature at a cooling rate of 5°C / hour. The polytetrafluoroethylene lining is removed and the excess solution is poured out to obtain Cs2Zr 0.25 Sn 0.75 Cl6:0.01Te 4+ Solid solution materials.

[0057] Figure 1 The Cs2Zr of Example 3 is given 0.25 Sn 0.75 Cl6:0.01Te 4+ X-ray diffraction pattern of solid solution material. Figure 1 It can be seen that its X-ray diffraction pattern is similar to that of the standard substance Cs2SnCl6 (PDF#70-2413). 0.25 Sn 0.75 Cl6:0.01Te 4+ The solid solution material has the same crystal structure as Cs2SnCl6. 4+ The doping does not introduce impurity phases.

[0058] Figure 2 The Cs2Zr of Example 3 is given0.25 Sn 0.75 Cl6:0.01Te 4+ Thermoluminescence curve of solid solution material after being excited by X-rays. Its thermoluminescence spectrum mainly consists of two thermoluminescence spectrum bands with temperature peaks at ~142K and ~203K. The thermoluminescence spectrum covers a wide temperature range from 100K to 350K. 0.25 Sn 0.75 Cl6:0.01Te 4+ The integrated thermoluminescence intensity of the solid solution material is commercial Y2O2S:Eu 3+ This shows that the Cs2Zr 0.25 Sn 0.75 Cl6:0.01Te 4 + Solid solution materials have high X-ray induced carrier storage properties.

[0059] Figure 7 The Cs2Zr of Example 3 is given 0.25 Sn 0.75 Cl6:0.01Te 4+ Thermoluminescence emission spectrum of solid solution optical storage material after being excited by X-rays. At 147K, the emission spectrum consists of Te 4+ The characteristic emission is composed of a shoulder-shaped emission band with a peak at ~750nm. At 210K, the emission spectrum is mainly composed of Te with a peak at ~582nm 4+ Characteristic emission composition.

[0060] Example 4

[0061] Te-doped double perovskite Cs2Zr of Example 4 1-x Sn x Cl6 solid solution material is Cs2Zr 0.75 Sn 0.25 Cl6:0.1Te 4 + Based on its chemical formula, the synthesis of Cs2Zr was calculated. 0.75 Sn 0.25 Cl6:0.1Te 4+ The chemical raw materials required are: 0.3367 grams of cesium chloride (CsCl), 0.1768 grams of zirconium chloride (ZrCl4), 0.0651 grams of tin chloride (SnCl4), 0.01596 grams of tellurium dioxide (TeO2) and 8 mL of hydrochloric acid with a concentration of 12 mol / L.

[0062] The preparation method thereof comprises the following steps:

[0063] (1) In a nitrogen-protected glove box, accurately weigh the required 0.3367 g of cesium chloride (CsCl), 0.1768 g of zirconium chloride (ZrCl4), 0.0651 g of tin chloride (SnCl4), and 0.01596 g of tellurium dioxide (TeO2). The above chemical raw materials are placed in a small glass bottle, and 8 mL of 12 mol / L hydrochloric acid is quickly added in an air atmosphere.

[0064] (2) The raw materials in the glass bottle are first mixed thoroughly and then transferred to the liner of the hydrothermal reactor. The reactor is placed in a high-temperature oven for heat treatment. The temperature of the oven is set as follows: after 1 hour, the oven is heated from room temperature to 180 degrees Celsius, kept at 180 degrees Celsius for 10 hours, and then cooled from 180 degrees Celsius to room temperature after 10 hours. The polytetrafluoroethylene liner is removed and the excess solution is poured out to obtain Cs2Zr 0.75 Sn 0.25 Cl6:0.1Te 4+ Solid solution materials.

[0065] Figure 8 Given Cs2Zr 0.75 Sn 0.25 Cl6:0.1Te 4+ Thermoluminescence emission spectrum of solid solution materials. The test method of thermoluminescence emission spectrum is: 0.75 Sn 0.25 Cl6:0.1Te 4+ The solid solution material was ground and pressed into a thin sheet with a mass of about 0.1 g; the sample was cooled to 100 Kelvin and excited with X-rays for 500 seconds; the sample was then gradually heated to 500 Kelvin at a heating rate of 1 Kelvin per second; the emission spectrum of the sample was recorded during the heating process. Figure 8 It can be seen that the emission spectrum of the sample consists of a broadband emission band with a peak wavelength of 582 nanometers. The thermoluminescence curve covers the temperature range from 100 Kelvin to 400 Kelvin. The thermoluminescence spectrum is a broadband spectrum with a peak at about 190 Kelvin.

[0066] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.

Claims

1. A Te-doped double perovskite Cs2Zr 1-x Sn x Cl6 solid solution material, characterized in that Its chemical formula is Cs2Zr 1- x Sn x Cl6:yTe 4+ , where 0<x<1, 0<y<0.

2.

2. The Te-doped double perovskite Cs2Zr as claimed in claim 1 1-x Sn x Cl6 solid solution material, characterized in that Its crystal structure is cubic and its space group is Fm3m.

3. Te-doped double perovskite Cs2Zr as claimed in claim 1 or 2 1-x Sn x Cl6 solid solution material, characterized in that The compound is obtained by heat-treating a cesium-containing compound, a zirconium-containing compound, a tin-containing compound, a chlorine-containing compound and a tellurium-containing compound, wherein the heat-treating temperature is 170-200° C. and the heat-treating time is 0.5-24 hours.

4. The Te-doped double perovskite Cs2Zr as claimed in claim 3 1-x Sn x Cl6 solid solution material, characterized in that The cesium-containing compound is cesium chloride and / or cesium carbonate, the zirconium-containing compound is zirconium chloride, the tin-containing compound is at least one of tin tetrachloride, tin dioxide and stannous oxide, the chlorine-containing compound is hydrochloric acid, and the tellurium-containing compound is tellurium dioxide and / or tellurium tetrachloride.

5. A Te-doped double perovskite Cs2Zr 1-x Sn x The preparation method of Cl6 solid solution material is characterized in that: The chemical formula of the Te-doped double perovskite solid solution material is Cs2Zr 1-x Sn x Cl6:yTe 4+ , wherein 0<x<1, 0<y<0.2, the preparation method comprises the following steps: (1) Weighing a cesium-containing compound, a zirconium-containing compound, a tin-containing compound, a chlorine-containing compound and a tellurium-containing compound in a molar ratio of 2:1-x:x:6:y; (2) The cesium-containing compound, the zirconium-containing compound, the tin-containing compound, the chlorine-containing compound and the tellurium-containing compound are mixed and placed in a sealed reaction container, and heat-treated at 170 to 200° C. for 0.5 to 24 hours. After cooling, the solids are separated and retained.

6. The preparation method according to claim 5, characterized in that: The specific operation of the heat treatment is as follows: heating from room temperature to 170-200°C at a heating rate of 1-3°C / min, keeping the temperature for 0.5-24 hours, and then cooling down to room temperature at a cooling rate of 2-20°C / hour.

7. The preparation method according to claim 5 or 6, characterized in that: The cesium-containing compound is cesium chloride and / or cesium carbonate, the zirconium-containing compound is zirconium chloride, the tin-containing compound is at least one of tin tetrachloride, tin dioxide and stannous oxide, the chlorine-containing compound is hydrochloric acid, and the tellurium-containing compound is tellurium dioxide and / or tellurium tetrachloride.

8. The preparation method according to claim 5 or 6, characterized in that: The cesium-containing compound, the zirconium-containing compound and the tin-containing compound in the step (1) are weighed in a protective nitrogen atmosphere.

9. The Te-doped double perovskite Cs2Zr according to any one of claims 1 to 4 1-x Sn x Application of Cl6 solid solution materials in the preparation of optical storage materials.

10. An optical storage material, characterized in that: The raw material comprises the Te-doped double perovskite Cs2Zr as claimed in any one of claims 1 to 4. 1-x Sn x Cl6 solid solution material.

Citation Information

Patent Citations

  • Preparation method and application of Zr &lt; 4 + &gt; doped Cs2SnCl6: 5% Te vacancy ordered double perovskite fluorescent powder

    CN117965163A